Factores de riesgos y su relación en desgarros de isquiotibiales en futbolistas masculinos del Club Deportivo Especializado Profesional Santa Rita, Cantón Vinces, provincia de Los Ríos, periodo junio-septiembre 2024. - Alban Robinson, Elva Eduvith (2024)
Muscle injuries, especially hamstring tears, are a major concern in the field of professional sports. This degree project has awakened our interest in investigating this problem, with the general objective of identifying the risk factors and their relationship in hamstring tears in male soccer players of the specialized professional sports club Santa Rita, Canton Vinces, province of Los Rios, period June-September 2024. Worldwide, muscle strain injuries in soccer constitute 31% of all cases, and up to 37% of players experience absences from training and/or matches during a season due to muscle injury. The specialized professional sports club Santa Rita Deportivo in the province of Los Ríos, Cantón Vinces has registered an increase in cases of injuries among soccer players. This situation has drawn the attention of the club's technical and medical staff, who have made efforts to identify risk factors, in order to prevent and treat these pathologies. This study will therefore be descriptive and field-based and will focus on analyzing the risk factors and their occurrence in hamstring tears in soccer players. Using a deductive method, the possible causes of these tears will be determined from direct observation of the players' environment. The research will combine quantitative and qualitative methods so that the results can be obtained through graphs and detailed analysis. It is hoped that our research will contribute to the improvement of this situation not only in the Santa Rita Sports Club, but also in every national and international soccer team.